Transcriptional target-based expression cloning of immunoregulatory molecules - Lamason, Rebecca L. (2010)
Immunologic research has benefited tremendously from expression-cloning strategies designed to isolate genes responsible for a wide variety of immunomodulatory activities, including cytokines, receptors, signaling proteins, and transcription factors. Here, we discuss the use of expression-cloning strategies that have been modified to detect cDNAs that influence gene expression as assayed by a transcriptional reporter. We summarize our experience with these screens, review important parameters, and discuss potential modifications.